Numerical study of particles trajectories in a multifunctional electrostatic separator powered by photovoltaic system - Guettaf, N.; Guettaf, S. E. I.; Zeghloul, T.; Nouri, H. (Національний технічний університет "Харківський політехнічний інститут", 2026)
Electrostatic separation is a growing technology in the recycling industry. It is an effective technology for processing plastics and metallic materials in the form of granular mixtures or fine powders from waste electrical and electronic equipment. The goal of the work is to represent graphically the trajectories of two insulating charged polypropylene particles of different sizes (2 mm and 4 mm) in the multifunctional electrostatic separator powered by photovoltaic (PV) system use a multipoint electrodes as charging device employing numerical simulation and demonstrate its effectiveness and reliability for the study of particles trajectories by integrating PV panels as a power source for electrostatic separators according to the recommendations of the new energy system.

Електростатична сепарація є технологією, що розвивається в індустрії переробки. Це ефективна технологія для переробки пластику та металевих матеріалів у вигляді гранульованих сумішей або тонких порошків із відходів електричного та електронного обладнання. Мета статті полягає у графічному представленні траєкторії двох ізолюючих заряджених частинок поліпропілену різних розмірів (2 мм і 4 мм) в багатофункціональному електростатичному сепараторі, що працює від фотоелектричної (PV) системи, використовуючи багатоточкові електроди як зарядний пристрій, застосовуючи чисельне моделювання та демонструючи ефективність PV панелей як джерела живлення для електростатичних сепараторів відповідно до рекомендацій нової енергетичної системи.
Keywords: electrostatic separation; electric field; photovoltaic system; numerical modeling; particle trajectories; waste electrical and electronic equipment; електростатична сепарація; електричне поле; фотоелектричні системи; чисельні моделювання; траєкторії частинок; відходи електричного обладнання; відходи електронного обладнання